Comparing and selecting performance measures using rank correlations - Massimiliano Caporin; Francesco Lisi (Economics: The Open-Access, Open-Assessment E-Journal, 2011)
The financial economics literature proposes dozens of performance measures to be used, for instance, to compare, analyse, rank and select assets. There is thus a problem: which measures should be considered? We extend the current literature by comparing a large set of performance measures over more than one thousand of equities included in the Standard & Poor's 1500 index. We evaluate performance measures by mean of rank correlations, exploiting the possible dynamic evolution of the rank correlations, and proposing a method for the identification of the subset of measures which are not equivalent. Our empirical study highlights that recent and more flexible measures provide different asset ranks compared to classical approaches, and that the set of equivalent performance measures is not stable over time.
Keywords: C10; C40; G11; 330; performance measurement; rank correlations; comparing performance measures